A triphenylamine-thiophene conductive polymer and its preparation method and application

Through the design of the new X-type triphenylamine-thiophene derivative and the preparation of electrochemical polymerization, the problems of existing conductive polymer film non-loose structure and inconvenient electrolyte embedding are solved, and efficient charge storage and excellent supercapacitor performance are achieved.

CN115881446BActive Publication Date: 2025-03-21ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211576550.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2025-03-21
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

The conductive polymer formed by the polymerization of Y-type monomers constructed by trianiline and thiophene derivatives has problems such as poor solubility and unloose polymer film structure, which leads to inconvenient insertion and removal of electrolyte ions and affects energy storage properties.

Method used

The new X-type triphenylamine-thiophene derivative is used to connect two triphenylamine derivative molecules through EDOT to construct a conductive polymer film with a larger molecular torsion angle. It is prepared by electrochemical polymerization to improve the loose structure and charge storage performance of the polymer.

Benefits of technology

The loose structure of the conductive polymer film is realized, the embedding and disengagement of electrolyte ions is promoted, the charge storage properties and the performance of supercapacitors are significantly improved, and the charge and discharge performance and cycle stability are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115881446B_ABST
    Figure CN115881446B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of supercapacitor electrode materials, and provides a triphenylamine-thiophene conductive polymer, wherein the preparation method is as follows: firstly, an X-type triphenylamine-thiophene derivative (TTPAE or ETPAE or BTTPAE) and a supporting electrolyte are dissolved in a solvent, and then a film is formed by cyclic voltammetry electrochemical polymerization, and then a target product is obtained after dedoping, washing, and drying. The surface structure of the prepared triphenylamine-thiophene conductive polymer film is loose, which is conducive to the embedding and extraction of electrolyte ions, and is conducive to storing more charges, and has excellent supercapacitor performance. It is made into an electrode material and applied to the field of supercapacitors, showing excellent energy storage properties and having potential application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of supercapacitor electrode materials, and in particular to a triphenylamine-thiophene conductive polymer supercapacitor material and a preparation method and application thereof. Background Art

[0002] Supercapacitors are one of the important research directions of new energy storage devices. Compared with traditional capacitors and batteries, they have unique advantages, such as large specific capacity, high power density, and long life, and are gradually attracting the interest of researchers. As one of the main electrode materials of supercapacitors, high molecular conductive polymer materials stand out among many electrode materials because of their high specific capacity, high conductivity, easy synthesis, and low cost during redox.

[0003] Triphenylamine and thiophene organic compounds are excellent hole transport materials that have been widely studied and applied in organic optoelectronic materials and solar cells. Since the triphenylamine structure itself has a high redox potential, the polymer material can have a wide voltage window, high energy density and power density. Thiophene and its derivatives are a five-membered heterocyclic structure with cheap raw materials and easy polymerization. They are often used as polymer groups in conductive polymer electrode materials.

[0004] The Y-type monomer constructed with triphenylamine and thiophene derivatives has been widely studied because it has three polymerizable active sites and has shown excellent energy storage properties in the application field of supercapacitor materials. Although the Y-type monomer has three polymerizable active sites, it is easy to polymerize and can construct cross-linked conductive polymers, but the solubility of most existing Y-type monomers is not very ideal, and the structure of the cross-linked conductive polymer film formed by polymerization is not loose enough, which is not conducive to the efficient embedding and extraction of ions in the polymer. Summary of the invention

[0005] The present invention aims to overcome the defects and shortcomings of the conductive polymer formed by polymerization of Y-type monomers constructed by triphenylamine and thiophene derivatives in the prior art. On the basis of a series of novel X-type triphenylamine-thiophene derivatives, the present invention provides a conductive polymer film prepared from novel X-type triphenylamine-thiophene derivatives. The conductive polymer film has a loose structure, can realize rapid embedding and extraction of electrolyte ions in the conductive polymer, and improves the charge storage property, so that it can be used to prepare a supercapacitor electrode material with excellent performance.

[0006] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:

[0007] A triphenylamine-thiophene conductive polymer, the structural formula of the polymer is:

[0008]

[0009] Among them, R in the structural formula is or or , n represents the average degree of polymerization, and n ranges from 10 to 2000.

[0010] In view of the shortcomings of the number of polymerizable active sites, solubility and structure of the Y-type monomer constructed by triphenylamine and thiophene derivatives in the prior art when polymerizing to form a conductive polymer, it is considered to improve the number of monomer active sites and solubility while making a triphenylamine-thiophene conductive polymer with a large spatial structural torsion angle, so that the conductive polymer film can have a loose morphology, accelerate the insertion and extraction of electrolyte ions, and store more charges, so as to be used to prepare high-performance supercapacitor materials. There are no relevant reports on the research on polymerizing a new type of X-type triphenylamine-thiophene derivative with a torsionable internal structure to form a conductive polymer and using it as an electrode material, which can become a research direction.

[0011] The present invention modifies a series of thiophene derivatives on the triphenylamine group, connects two triphenylamine derivative molecules through EDOT (3,4-ethylenedioxythiophene), thereby constructing a series of novel triphenylamine-based X-type thiophene derivatives, and further prepares the conductive polymer film by electrochemical polymerization. Since an EDOT molecule is introduced into the center of the triphenylamine-based X-type thiophene derivative, it can bring about a greater twist in the internal structure of the molecule, making the surface structure of the X-type triphenylamine-thiophene conductive polymer film loose, which is conducive to the embedding and extraction of electrolyte ions, and is conducive to storing more charges, and has excellent supercapacitor performance. In the constant current charge and discharge test, it was found that the film has symmetrical constant current charge and discharge properties. When the current density is 5 mA / cm 3 When the area specific capacitance is as high as 180.1 mF / cm 3 Since the film exhibits excellent energy storage properties, it can be applied to the field of supercapacitors and has potential application value.

[0012] A method for preparing a triphenylamine-thiophene conductive polymer comprises the following steps:

[0013] (1) dissolving the X-type triphenylamine-thiophene derivative and the supporting electrolyte in a solvent;

[0014] (2) Cyclic voltammetry electrochemical polymerization film formation;

[0015] (3) Dedoping, cleaning, and drying to obtain the target product.

[0016] Preferably, the structural formula of the X-type triphenylamine-thiophene derivative is:

[0017] ,

[0018] Among them, R in the structural formula is or or .

[0019] According to the different substituents R, X-type triphenylamine-thiophene derivatives can be divided into three types: TTPAE, ETPAE, and BTTPAE, and their structures are shown below:

[0020] .

[0021] Preferably, the concentration of the X-type triphenylamine-thiophene derivative is 0.5-1 mmol / L.

[0022] Preferably, the supporting electrolyte is one of tetrabutylammonium hexafluorophosphate, tetrabutylammonium perchlorate, lithium tetrafluoroborate and lithium perchlorate.

[0023] Preferably, the solvent is one of chromatographic grade dichloromethane, chromatographic grade acetonitrile and propylene carbonate.

[0024] Adding an appropriate amount of supporting electrolyte to the reactants can improve the conductivity of the reaction system, thereby promoting the occurrence of electrochemical polymerization. As the supporting electrolyte of the reaction system, one of tetrabutylammonium hexafluorophosphate, tetrabutylammonium perchlorate, lithium tetrafluoroborate, and lithium perchlorate can be selected. It has been found through experiments that the preparation effect of the polymer is better when tetrabutylammonium hexafluorophosphate is used as the supporting electrolyte in this polymerization reaction system. As the solvent of this polymerization reaction system, one of dichloromethane, acetonitrile, and propylene carbonate can be selected. In the experiment, when chromatographic grade dichloromethane is used as the solvent, the preparation effect of the polymer is better.

[0025] Preferably, the voltage range of the cyclic voltammetry electrochemical polymerization in step (2) is 0-1.2 V, and the number of cyclic voltammetry polymerization cycles is 6-10 cycles.

[0026] Preferably, the dedoping conditions are voltage -0.8 to -0.5 V and time 30 to 60 s.

[0027] The invention dissolves an X-type triphenylamine-thiophene derivative in a chromatographic grade dichloromethane solvent with a concentration of 0.5-1 mmol / L, and adds tetrabutylammonium hexafluorophosphate as a supporting electrolyte with a concentration of 0.05-0.1 mol / L, and forms a film through cyclic voltammetry electrochemical polymerization, wherein the voltage range is 0-1.2 V, the number of cyclic voltammetry polymerization cycles is 6-10 cycles, and the scanning rate is 100 mV / s. After the polymerization is completed, the film is dedoped in a blank electrolyte solution (0.1 mol / L tetrabutylammonium hexafluorophosphate / dichloromethane) (30s-60s, -0.8--0.5V), and then the polymer film is washed with a chromatographic grade mixed solution of dichloromethane:acetonitrile=2:3, and dried at 50°C for two hours to obtain a triphenylamine-thiophene conductive polymer.

[0028] The triphenylamine-thiophene conductive polymer is used in preparing electrode materials.

[0029] The triphenylamine-thiophene conductive polymer is used in the manufacture of supercapacitors.

[0030] In order to test the performance of the prepared triphenylamine-thiophene conductive polymer as an electrode material, the charge and discharge performance of the polymer film was tested using an electrochemical workstation. Specifically, a dichloromethane solution of tetrabutylammonium hexafluorophosphate was used as the electrolyte solution, a conductive polymer film was used as the working electrode, a platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode to form a three-electrode system. The charge and discharge performance of the material was tested at different charge and discharge current densities. The test results show that the prepared conductive polymer has better charge and discharge performance. When the current density is 5 mA / cm 3 When the area specific capacitance is as high as 180.1 mF / cm 3 , and has good charge and discharge cycle stability.

[0031] The present invention has the following beneficial effects:

[0032] (1) An EDOT molecule is introduced into the center of the monomer chemical structure of the triphenylamine-thiophene conductive polymer prepared by the present invention, which can bring a larger torsion angle to the internal structure of the molecule, making the structure of the prepared polymer film looser;

[0033] (2) Since the surface structure of the triphenylamine-thiophene conductive polymer film is loose, it is easy to embed and remove electrolyte ions. The loose surface morphology is also easy to store more charges, which greatly improves the electrochemical properties of the triphenylamine-thiophene derivative polymer film material;

[0034] (3) The triphenylamine-thiophene conductive polymer film has better charge and discharge performance. 3When the area specific capacitance is as high as 180.1 mF / cm 3 , and has good charge and discharge cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the cyclic voltammetric polymerization curve of triphenylamine-thiophene derivatives (TTPAE) in Example 2 of the present invention.

[0036] Figure 2 This is the cyclic voltammetric polymerization curve of triphenylamine-bithiophene derivatives (BTTPAE) in Example 3 of the present invention.

[0037] Figure 3 This is the cyclic voltammetric polymerization curve of triphenylamine-bithiophene derivatives (BTTPAE) in Example 4 of the present invention.

[0038] Figure 4 This is the cyclic voltammetric polymerization curve of the triphenylamine-bithiophene derivative (BTTPAE) in Example 5 of the present invention.

[0039] Figure 5 This is the cyclic voltammetric polymerization curve of the triphenylamine-EDOT derivative (ETPAE) in Example 6 of the present invention.

[0040] Figure 6 1 is the cyclic voltammetry curve of the triphenylamine-bithiophene conductive polymer film (pBTTPAE) in Example 7 of the present invention.

[0041] Figure 7 This is the constant current charge and discharge curve of the triphenylamine-bithiophene conductive polymer film (pBTTPAE) in Example 8 of the present invention.

[0042] Figure 8 This is a constant current charge-discharge stability curve of the triphenylamine-bithiophene conductive polymer film (pBTTPAE) in Example 9 of the present invention.

[0043] Fig. 9 It is a comparison curve of the charge and discharge performance test of pBTTPAE and pTEPA in Example 10 of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0045] Example 1: Synthesis of an X-type triphenylamine-thiophene derivative (taking the synthesis of BTTPAE (triphenylamine-dithiophene derivative) as an example)

[0046] (1) Synthesis of intermediate reactant TPA-2BT

[0047] Tri-(4-bromo)-triphenylamine (600 mg, 1.25 mmol) and an appropriate amount of bis(triphenylphosphine)palladium dichloride were added to a single-mouth round-bottom flask in sequence. Under N2 protection, N, N-dimethylformamide (20 mL) was added as the reaction solvent. Thiophene tin compound (2.25 mmol) was then added to the reaction flask, stirred, and heated to reflux at 120 °C for 18 hours. After the reaction was completed, the reaction solution was poured into 200 mL of deionized water and extracted with 400 mL of dichloromethane for 5 times until the solvent N, N-dimethylformamide was extracted cleanly. After the extract was concentrated, it was dried with anhydrous sodium sulfate to remove water. After mixing with coarse silica gel, it was purified by column chromatography with fine silica gel as the stationary phase and dichloromethane and petroleum ether as the mobile phase. The eluent containing the target compound was collected, the solvent was removed by rotary evaporation and dried to obtain the pure product TPA-2BT (the structure of TPA-2BT is , R in the structure is );

[0048] (2) Synthesis of BTTPAE (triphenylamine-dithiophene derivative)

[0049] TPA-2BT (650 mg, 1 mmol) prepared in Example 1 and an appropriate amount of bis(triphenylphosphine)palladium dichloride were added to a 100 mL two-necked round-bottom flask in sequence. Under N2 protection, N, N-dimethylformamide (20 mL) was added as a reaction solvent, and then double-sided tin EDOT (0.41 mol) was added to the reaction flask, stirred, and heated to reflux at 120°C for 18 hours. After the reaction was completed, the reaction solution was poured into 200 mL of deionized water and extracted with 400 mL of dichloromethane for 5 times until the solvent N, N-dimethylformamide was extracted cleanly. After the extract was concentrated, it was dried with anhydrous sodium sulfate to remove water, and after mixing with coarse silica gel, it was purified by column chromatography with fine silica gel as the stationary phase and dichloromethane and petroleum ether as the mobile phase. The eluent containing the target compound was collected, the solvent was removed by rotary evaporation and dried to obtain the pure product BTTPAE.

[0050] Example 2: Preparation of triphenylamine-thiophene conductive polymer (pTTPAE)

[0051] 9.7 mg (1 mmol / L) of the monomer of triphenylamine-based X-type thiophene derivative (TTPAE) was added to a 10 mL volumetric flask, and 0.387 g (0.1 mol / L) of tetrabutylammonium hexafluorophosphate was added as a supporting electrolyte. The volume was fixed with chromatographic grade dichloromethane, and ultrasonic treatment was performed for 3 min. After the solid was completely dissolved, cyclic voltammetric electrochemical polymerization was performed. The specific process was as follows: ITO glass (0.9×4 cm) was used as the working electrode, platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The polymerization voltage window was 0~1.2 V, and the number of polymerization cycles was 5 cycles. After the polymerization was completed, the polymer film was dedoped in a blank electrolyte solution (0.1 mol / L tetrabutylammonium hexafluorophosphate / dichloromethane) for 60 s (voltage -0.5 V), and then the polymer film was washed with a chromatographic grade mixed solution of dichloromethane: acetonitrile = 2: 3, and dried at 50 °C for two hours. The cyclic voltammetric polymerization curve is shown in the figure. Figure 1 shown.

[0052] like Figure 1 As shown, with the increase of polymerization cycles, the peak current intensity of the polymer gradually increases, indicating that the polymer is successfully deposited on the ITO conductive glass.

[0053] Example 3: Preparation of triphenylamine-bithiophene conductive polymer (pBTTPAE)

[0054] 6.4 mg (0.5 mmol / L) of the monomer of triphenylamine-based X-type thiophene derivative (BTTPAE) was added to a 10 mL volumetric flask, and 0.387 g (0.1 mol / L) of tetrabutylammonium hexafluorophosphate was added as a supporting electrolyte. The volume was fixed with chromatographic grade dichloromethane, and ultrasonic treatment was performed for 3 min. After the solid was completely dissolved, cyclic voltammetric electrochemical polymerization was performed. The specific process was as follows: ITO glass (0.9×4 cm) was used as the working electrode, platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The polymerization voltage window was 0~1.2 V, and the number of polymerization cycles was 6 cycles. After the polymerization was completed, the film was dedoped in a blank electrolyte solution (0.1 mol / L tetrabutylammonium hexafluorophosphate / dichloromethane) for 30 s (voltage -0.5 V), and then the polymer film was washed with a chromatographic grade mixed solution of dichloromethane: acetonitrile = 2: 3, and dried at 50 °C for two hours. The cyclic voltammetric polymerization curve is shown in the figure. Figure 2 shown.

[0055] like Figure 2 As shown, with the increase of polymerization cycles, the peak current intensity of the polymer gradually increases, indicating that the polymer is successfully deposited on the ITO conductive glass.

[0056] Example 4: Preparation of triphenylamine-bithiophene conductive polymer (pBTTPAE)

[0057] 10.2 mg (0.8 mmol / L) of the monomer of triphenylamine-based X-type thiophene derivative (BTTPAE) was added to a 10 mL volumetric flask, and 0.387 g (0.1 mol / L) of tetrabutylammonium hexafluorophosphate was added as a supporting electrolyte. The volume was fixed with chromatographic grade dichloromethane, and ultrasonic treatment was performed for 3 min. After the solid was completely dissolved, cyclic voltammetric electrochemical polymerization was performed. The specific process was as follows: ITO glass (0.9×4 cm) was used as the working electrode, platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The polymerization voltage window was 0~1.2 V, and the number of polymerization cycles was 8 cycles. After the polymerization was completed, the polymer film was dedoped in a blank electrolyte solution (0.1 mol / L tetrabutylammonium hexafluorophosphate / dichloromethane) for 50 s (voltage -0.6 V), and then the polymer film was washed with a chromatographic grade mixed solution of dichloromethane: acetonitrile = 2: 3, and dried at 50 °C for two hours. The cyclic voltammetric polymerization curve is shown in the figure. Figure 3 shown.

[0058] like Figure 3 As shown, with the increase of polymerization cycles, the peak current intensity of the polymer gradually increases, indicating that the polymer is successfully deposited on the ITO conductive glass.

[0059] Example 5: Preparation of triphenylamine-bithiophene conductive polymer (pBTTPAE)

[0060] 12.8 mg (1 mmol / L) of the monomer of triphenylamine-based X-type thiophene derivative (BTTPAE) was added to a 10 mL volumetric flask, and 0.387 g (0.1 mol / L) of tetrabutylammonium hexafluorophosphate was added as a supporting electrolyte. The volume was fixed with chromatographic grade dichloromethane, and ultrasonic treatment was performed for 3 min. After the solid was completely dissolved, cyclic voltammetric electrochemical polymerization was performed. The specific process was as follows: ITO glass (0.9×4 cm) was used as the working electrode, platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The polymerization voltage window was 0~1.2 V, and the number of polymerization cycles was 10 cycles. After the polymerization was completed, the polymer film was dedoped in a blank electrolyte solution (0.1 mol / L tetrabutylammonium hexafluorophosphate / dichloromethane) for 30 s (voltage -0.8 V), and then the polymer film was washed with a chromatographic grade mixed solution of dichloromethane: acetonitrile = 2: 3, and dried at 50 °C for two hours. The cyclic voltammetric polymerization curve is shown in the figure. Figure 4 shown.

[0061] like Figure 4 As shown, with the increase of polymerization cycles, the peak current intensity of the polymer gradually increases, indicating that the polymer is successfully deposited on the ITO conductive glass.

[0062] Example 6: Preparation of triphenylamine-EDOT conductive polymer (pETPAE)

[0063] 11.9 mg (1 mmol / L) of the monomer of triphenylamine-based X-type thiophene derivative (ETPAE) was added to a 10 mL volumetric flask, and 0.387 g (0.1 mol / L) of tetrabutylammonium hexafluorophosphate was added as a supporting electrolyte. The volume was fixed with chromatographic grade dichloromethane, and ultrasonic treatment was performed for 3 min. After the solid was completely dissolved, cyclic voltammetry electrochemical polymerization was performed. The specific process was as follows: ITO glass (0.9×4 cm) was used as the working electrode, platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The polymerization voltage window was 0~1.2 V, and the number of polymerization cycles was 5 cycles. After the polymerization was completed, the polymer film was dedoped in a blank electrolyte solution (0.1 mol / L tetrabutylammonium hexafluorophosphate / dichloromethane) for 30 s (voltage -0.5 V), and then the polymer film was washed with a chromatographic grade mixed solution of dichloromethane: acetonitrile = 2: 3, and dried at 50 °C for two hours. The cyclic voltammetry polymerization curve is shown in the figure. Figure 5 shown.

[0064] like Figure 5 As shown, with the increase of polymerization cycles, the peak current intensity of the polymer gradually increases, indicating that the polymer is successfully deposited on the ITO conductive glass.

[0065] Example 7: Cyclic voltammetry performance test of triphenylamine-bithiophene conductive polymer (pBTTPAE)

[0066] The electrochemical workstation was used to test the cyclic voltammetry electrochemical performance of the film. The test method was as follows: 0.387 g of tetrabutylammonium hexafluorophosphate was added to a 10 mL volumetric flask, and the volume was fixed with chromatographic grade dichloromethane, which was used as a blank supporting electrolyte solution. The blank electrolyte solution was used as the test solution, the polymer film was used as the working electrode, the platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode to form a three-electrode system. The test voltage window was 0.4 V-1.4 V, and the scan rates were 30 mV / s, 50 mV / s, 100 mV / s, 200 mV / s and 300 mV / s, respectively. The test results are shown in Figure 1. Figure 6 shown.

[0067] like Figure 6 As shown in the figure, the peak current intensity of the polymer gradually increases with the increase of the scanning rate, and there is a good linear relationship between the redox peak current and the scanning rate, indicating that the polymer film can adhere well to the ITO surface. It also shows that the redox process of the polymer is reversible and its electrochemical process is controlled by non-diffusion.

[0068] Example 8: Test of the charge and discharge performance of triphenylamine-bithiophene conductive polymer (pBTTPAE) as a supercapacitor material

[0069] The charge and discharge performance of the film was tested using an electrochemical workstation. The test method was as follows: 0.387 g of tetrabutylammonium hexafluorophosphate was added to a 10 mL volumetric flask and fixed to volume with chromatographic grade dichloromethane, which was used as a blank supporting electrolyte solution. The blank electrolyte solution was used as the test solution, the polymer film was used as the working electrode, the platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode to form a three-electrode system. The test voltage window was 0.4 V to 1.4 V, and the current density was 5 mA / cm 3 , 10mA / cm 3 , 20 mA / cm 3 , 30 mA / cm 3 , 40 mA / cm 3 and 50 mA / cm 3 The charge and discharge performance of the film was tested under constant current conditions. The test results are as follows Figure 7 shown.

[0070] like Figure 7 As shown in the figure, the constant current charge-discharge curves of the polymer show obvious supercapacitive properties, and the calculated results are 5 A / cm 3 , 10 A / cm 3 , 20 A / cm 3 , 30 A / cm 3 , 40 A / cm 3 and 50 A / cm 3 Its volumetric capacity is 324.4 F / cm at a current density of 3 , 319.8 F / cm 3 , 316.2 F / cm 3 , 309.1 F / cm 3 , 304.2 F / cm 3 and 292.2 F / cm 3 , the polymer has a higher volumetric capacity and better charge and discharge rate performance.

[0071] Example 9: Test on the charge and discharge stability of triphenylamine-dithiophene conductive polymer (pBTTPAE) as a supercapacitor material

[0072] The charge and discharge stability of the film was tested using an electrochemical workstation. The test method was as follows: 0.387 g of tetrabutylammonium hexafluorophosphate was added to a 10 mL volumetric flask, and the volume was fixed with chromatographic grade dichloromethane, which was used as a blank supporting electrolyte solution. The blank electrolyte solution was used as the test solution, the polymer film was used as the working electrode, the platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode to form a three-electrode system. The test voltage window was 0.4 V to 1.4 V, and the current density was 10 mA / cm 3 The charge and discharge stability of the film was tested under constant current conditions. The test results are as follows Figure 8 shown.

[0073] like Figure 8 As shown, the polymer exhibits good charge and discharge stability. After 200 cycles of constant current charge and discharge, the volumetric capacity of the polymer remains more than 80% of the initial volumetric capacity.

[0074] Example 10: Comparative test of charge and discharge performance of pBTTPAE and pTEPA

[0075] The charge and discharge performance of the two polymer films was tested using the same preparation method and test method. The test method is as follows: 0.387 g of tetrabutylammonium hexafluorophosphate was added to a 10 mL volumetric flask, and the volume was fixed with chromatographic grade dichloromethane, which was used as a blank supporting electrolyte solution. The blank electrolyte solution was used as the test solution, the polymer film was used as the working electrode, the platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode to form a three-electrode system. The test voltage window was 0.4 V~1.4 V, and the current density was 5 A / cm 3 The test results are as follows: Fig. 9 shown.

[0076] The monomer (Y-type) structure of the comparative polymer pTEPA is:

[0077]

[0078] like Fig. 9 As shown, by comparison, it is found that at a current density of 5 A / cm 3 When the volumetric specific capacitance of pETPAE and pTEPA is 324.4 F / cm 3 and 286.2 F / cm 3 , pBTTPAE showed a higher specific capacity than pTEPA, and pBTTPAE showed a wider voltage window. In summary, the new X-type monomer molecules were designed and synthesized based on triphenylamine-thiophene, and the conductive polymers prepared further had excellent energy storage properties, which is of great significance for the preparation of high-performance energy storage materials and their applications.

Claims

1. A triphenylamine-thiophene conductive polymer, characterized in that: The structural formula of the polymer is: Among them, R in the structural formula is or or , n represents the average degree of polymerization, and n ranges from 10 to 2000.

2. A method for preparing a triphenylamine-thiophene conductive polymer as claimed in claim 1, characterized in that: The following steps are involved: (1) dissolving the X-type triphenylamine-thiophene derivative and the supporting electrolyte in a solvent; (2) Cyclic voltammetry electrochemical polymerization film formation; (3) Dedoping, cleaning, and drying to obtain the target product.

3. The method for preparing a triphenylamine-thiophene conductive polymer according to claim 2, characterized in that: The structural formula of the X-type triphenylamine-thiophene derivative is: , where R in the structural formula is or or .

4. A method for preparing a triphenylamine-thiophene conductive polymer as claimed in claim 2 or 3, characterized in that: The concentration of the X-type triphenylamine-thiophene derivative is 0.5-1 mmol / L.

5. The method for preparing a triphenylamine-thiophene conductive polymer according to claim 2, characterized in that: The supporting electrolyte is one of tetrabutylammonium hexafluorophosphate, tetrabutylammonium perchlorate, lithium tetrafluoroborate and lithium perchlorate.

6. The method for preparing a triphenylamine-thiophene conductive polymer according to claim 2, characterized in that: The solvent is one of chromatographic grade dichloromethane, chromatographic grade acetonitrile and propylene carbonate.

7. The method for preparing a triphenylamine-thiophene conductive polymer according to claim 2, characterized in that: The voltage range of the cyclic voltammetry electrochemical polymerization in the step (2) is 0-1.2 V, and the number of cyclic voltammetry polymerization cycles is 6-10 cycles.

8. The method for preparing a triphenylamine-thiophene conductive polymer according to claim 2, characterized in that: The dedoping conditions are voltage -0.8~-0.5 V and time 30~60 s.

9. Use of the triphenylamine-thiophene conductive polymer according to claim 1 in preparing electrode materials.

10. Use of the triphenylamine-thiophene conductive polymer according to claim 1 in making a supercapacitor.

Citation Information

Patent Citations

  • Polythiophene conductive polymer taking 9-phenyl-carbazole as central core and application thereof

    CN114783790A

  • Thiophene-based copolymer and method for synthesizing the same

    JP2016041780A